Virology, Clinical Features and Diagnosis of COVID 19: Review Analysis - Bhusal, L.; Amgain, K.; Dangal, G.; Tamang, P.D.; Shahi, P.; Budhathoki, P.; Paudel, A.K. (Kathmandu University Medical Journal, 2020)
COVID-19 requires unprecedented mobilization of the health systems to prevent the rapid spread of this unique virus, which spreads via respiratory droplet and causes respiratory disease. There is an urgent need for an accurate and rapid test method to quickly identify many infected patients and asymptomatic carriers to prevent virus transmission and assure timely treatment of the patients.This article aims as an outcome of review of the evidence on viral load and its virulence of SARS-CoV2, so that it will help in further understanding the fact useful for investigating and managing the COVID-19 cases.A search of available evidence was conducted in pub-med “COVID-19 viral load and virulence” and its associated characters world-wide and Google Scholar to capture the most recently published articles. The WHO and Centre for Disease Control and Prevention (CDC) database of publications on novel coronavirus were also screened for relevant publications. Abstracts of 55 articles were screened by two authors and 15 were included in this study based on the inclusion criteria.SARS-coV2, the causative agent of COVID-19 falls under the coronavirus family but it has higher infectivity compared to SARS and MERS with higher reproduction numbers (Ro). Virulence has been found to be different throughout the world, however lower compared to SARS and MERS, till date. The most common clinical features have been found to be cough and fever. RT PCR remains the most sensitive and specific method for the diagnosis of COVID-19 although it is time consuming, costly and requires highly skilled human resources. Hence, newer modalities like RT- LAMP can be alternative for point of care diagnosis as this is both cost effective and requires less skilled human resources.Despite recent advances in disease diagnosis and treatment outcomes using latest technological advances in molecular biology, the global pandemic COVID-19 remains a major headache for governments across the world due to limited testing capacity and lack of appropriate treatment and vaccine.